Interminable Long Memory Model And Its Hybrid For Time Series Modeling - Alhaji, Jibrin Sanusi (2019)
The financial and economic indices are nonstationary, long-range dependence and volatile. These are very serious problems because each affect the accuracy, validity and reliability of model fitting and the forecasting of the studied series. In view of this, our current study proposes fractional filter to decompose the nonstationary and Interminable Long Memory (ILM) time series with fractional differencing value in the interval of 1<